Genetic differentiation among ten populations of the genus Neoplecostomus (Teleostei: Loricariidae) from the upper Parana River basin - Monezi Lucena, Ana Luisa; Renesto, Erasmo; Oliveira, Claudio [UNESP]; Mateus, Rogerio Pincela; Zawadzki, Claudio Henrique (Pergamon-Elsevier B.V. Ltd, 2012)
Seven populations of the genus Neoplecostomus with undefined taxonomic status plus Neoplecostomus corumba, Neoplecostomus paranensis, and Neoplecostomus yapo were analyzed by means of allozyme electrophoresis technique. We performed electrophoretic analysis of six enzyme systems. Ten loci and 23 alleles were detected, showing similar banding patterns to those found for N. yapo. The index of heterozygosity showed an excess of homozygotes. N. paranensis showed no allelic variation and the Carandai population showed the highest expected heterozygosity (0.242). The analysis of the values of genetic identities and distances showed that most genetic similar populations were Monjolo and Sapucai (I = 0.958) and the most divergent populations were N. yapo and Cachoeira (I = 0.128). A dendrogram constructed through the similarity index and a cladogram yielded by Maximum Likelihood (ML) analysis of the allele frequencies were in general congruent. N. yapo was the most divergent species in the similarity dendrogram but clustered with the Casca d'Antas population in the ML analysis. The relationships of Carandai and Tamborete populations and that of N. corumba and Cachoeira and the close positioning of Sapucai, Monjolo, Espraiado and N. paranensis were revealed in both analysis. Our data reinforce the use of allozymes as an auxiliary tool for taxonomic and conservation studies on Neoplecostomus, as it reveals many putative genetically isolated populations. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Allozymes; Heterozygosity; Genetic variability; Neoplecostominae; Neotropical fishes